Implementation and effectiveness of transgender stigma reduction interventions in sub-Saharan Africa: a scoping review - Patience A. Muwanguzi; Paul K. Otiku; Racheal Nabunya; Blessings Gausi (Journal of Global Health Reports)
# Background